TINJAUAN YURIDIS PERJANJIAN PEMBORONGAN PEKERJAAN ANTARA PT ABC DAN PT XYZ - Yuhao, Sun; Indiraharti, Novina Sri (Fakultas Hukum Universitas Trisakti, 2023)
Engagement according to Prof. Subekti is a legal relationship between two people or two parties, based on which one party has the right to demand something from another party, and the other party is obliged to fulfill that demand. Apart from that, the terms of the contract itself are regulated in article 1313 of the Civil Code which explains that an agreement is